Neurodiversity and Orthodontic Treatment. (2nd July 2022) - Dillon, Maria; D'Souza, Edwina; Edwards, Ian
Abstract : 'Neurodiversity' is a term used to describe people with neurological variation; this includes people with autism, dyspraxia, dyslexia and attention deficit hyperactivity disorder. Studies have shown an increased prevalence of malocclusion and dental trauma in people with these conditions. Unfortunately, a lack of understanding around such neurological differences can create barriers when accessing orthodontic care. The aim of this article is to raise awareness around the subject and to suggest reasonable adjustments to practice which may subsequently be used by the orthodontic team to improve the patient experience. CPD/Clinical Relevance: Recognition of neurodiversity and the need to make reasonable adjustments to orthodontic care may aid compliance and improve outcomes in this group of patients.